Eksperimen Pembelajaran Matematika Dengan Strategi Discovery Learning Dan Inkuiri Terhadap Hasil Belajar Ditinjau Dari Kemandirian Belajar Pada Siswa Kelas VII SMP Negeri 2 Tulung Tahun Ajaran 2015/2016 - SUNDARI, Sundari (2016)
The objectives of the research are: (1) the contribution of Discovery Learning and inquiry toward the result of learning match.(2) the contribution of independence learning degree toward the result of learning match.(3) the interaction of Discovery Learning strategy and inquiry with independence learning degree toward the result of learning match. The design of the research was quasi experimental research with factorial design 2x3. The population was all students in class VII SMP Negeri 2 Tulung in Academic Year of 2015/2016. The sample of the research was two class which took cluster random sampling. The technique ofcollecting data by using docummentation, questionare and test. The technique of analysing data by using ANOVA and beforeit was used the researcher did assumption test. It was normality test and homogenity test. The result of the research where: (1) there is no contribution of discovery learning strategy and inquiry toward the result of learning match with α=5%, (2) there is no contribution ofindependence learning degree toward the result of learning match with α=5%,(3) there is no interaction between discovery learning strategy and inquiry with independence learning degree toward the result of learning match with α=5%.